Rational inattention, inflation developments and perceptions after the euro cash changeover - Michael Ehrmann (European Central Bank (ECB), 2006)
This paper uses the euro cash changeover to test theories of finite informationprocessing capacities on the side of consumers. It argues that the denomination of prices in a new currency has increased the information-processing requirements for consumers by more than for sellers, a wedge that can lead to price increases. The size of the wedge should depend on the complexity of the currency conversion rates. In line with this theory, the paper finds that the evolution of prices for food products around the cash changeover varied across countries, depending on the complexity of conversion rates. These changeover effects are found in particular for goods with prices below one euro sold in mid-priced stores. The paper also finds that cross-country differences in the mismatch of perceived and actual inflation in the aftermath of the cash changeover are linked to differences in the complexity of conversion rates.
Keywords: D84; E31; E58; L11; 330; euro cash changeover; perceived inflation; rational inattention; Inflationsrate; Inflationserwartung; Euro; Eurozone; EU-Staaten